Social Attitudes, Communication Skills, and Environmental Literacy of Middle School Students - Lia Astuti; Mimien Henie Irawati Al Muhdhar; Suhadi Suhadi; Ruchimah Achmad (Jurnal Pendidikan Sains, 2020)
Abstract: The purpose of the study was to analyze the social attitudes, communication skills, and environmental literacy of class XI students at SMAN 2 Malang. The type of research is mixed, through a quantitative approach to describe environmental literacy, and qualitative, to describe social attitudes. The research population is all students of class XI. The samples in this study were students of class XI science, the independent variables were students of class XI, the dependent variable was social attitudes, communication skills, and environmental literacy. The research instrument is a questionnaire. The analysis technique is that the research data is reduced, verified, and presented. The results showed that the scores were not balanced, the values of social attitudes, communication skills, and environmental literacy were scored 77.25, 75.75, and 75.67.Abstrak: Tujuan penelitian menganalisis sikap sosial, keterampilan komunikasi, dan literasi lingkungan siswa kelas XI di SMAN 2 Malang. Jenis penelitian yakni campuran, melalui pendekatan kuantitatif untuk menjabarkan literasi lingkungan, dan kualitatif, untuk menjabarkan sikap sosial. Populasi penelitian yakni seluruh siswa kelas XI. Sampel pada penelitian yakni siswa kelas XI IPA, variabel bebas siswa kelas XI, variabel terikat yakni sikap sosial, keterampilan komunikasi, dan literasi lingkungan. Instrumen penelitian yakni kuisioner. Teknik analisis yakni data hasil penelitian direduksi, diverifikasi, dan disajikan. Hasil penelitian menunjukkan bahwa nilai belum seimbang, nilai sikap sosial, keterampilan komunikasi, dan literasi lingkungan mendapat nilai yakni 77,25, 75,75, dan 75,67.